A head-to-head comparison of myocardial strain by fast-strain encoding and feature tracking imaging in acute myocardial infarction - El-Saadi, Walid; Engvall, Jan Edvin; Alfredsson, Joakim; Karlsson, Jan-Erik; Martins, Marcelo; Sederholm, Sofia; Faisal Zaman, Shaikh; Ebbers, Tino; Kihlberg, Johan (Frontiers in Cardiovascular Medicine, 2022)
Background: Myocardial infarction (MI) is a major cause of heart failure. Left ventricular adverse remodeling is common post MI. Several studies have demonstrated a correlation between reduced myocardial strain and the development of adverse remodeling. Cardiac magnetic resonance (CMR) with fast-strain encoding (fast-SENC) or feature tracking (FT) enables rapid assessment of myocardial deformation. The aim of this study was to establish a head-to-head comparison of fast-SENC and FT in post ST-elevated myocardial infarction (STEMI) patients, with clinical 2D speckle tracking echocardiography (2DEcho) as a reference. Methods: Thirty patients treated with primary percutaneous coronary intervention for STEMI were investigated. All participants underwent CMR examination with late gadolinium enhancement, cine-loop steady state free precession and fast-SENC imaging using a 1.5T scanner as well as a 2DEcho. Global longitudinal strain (GLS), segmental longitudinal strain (SLS), global circumferential strain (GCS) and segmental circumferential strain (SCS) were assessed along with the MI scar extent. Results: The GCS measurements from fast-SENC and FT were nearly identical: mean difference 0.01 (2.5) % (95% CI - 0.92 – 0.95). For GLS, fast-SENC values were higher than FT, with a mean difference of 1.8 (1.4) % (95% CI 1.31- 2.35). Tests of significance for GLS did not show any differences between the MR methods and 2DEcho. Average strain in the infarct-related artery (IRA) segments compared to the remote myocardium was significantly lower for the left anterior descending artery and right coronary artery culprits but not for the left circumflex artery culprits. Fast-SENC displayed a higher area under the curve for detecting infarcted segments than FT for both SCS and SLS. Conclusion: GLS and GCS did not differ significantly between fast-SENC and FT. Both showed acceptable agreement with 2DEcho for longitudinal strain. Segments perfused by the IRA showed significantly reduced strain values compared to the remote myocardium. Fast-SENC presented a higher sensitivity and specificity for detecting infarcted segments than FT.